IN MEMORIAM PROFESSOR PETRE T. FRANGOPOL, Ph.D., HONOR MEMBER OF THE ROMANIAN ACADEMY (1933-2020) - DAVID, Daniel (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Petre Frangopol was a top Romanian scientist, a member of the Romanian Academy, who, during his rich and productive scientific career, was also associated to our university.